Traditional oil miners reach their prosperity: an assessment of social welfare in Wonocolo, Indonesia - Yeti Ulfah Tuzyahroya; S Sariffuddin (Journal of Degraded and Mining Lands Management, 2020)
The purpose of this research was to determine the traditional oil and gas mining community welfare in Wonocolo, Kedewan, Bojonegoro. Welfare hierarchy will explain about needs fulfilment which is needed by the development planning process. The research used a mixed-method which is the result of scoring by quantitative analysis validated by the description of qualitative data. The results of this research indicated that the welfare hierarchy of the traditional oil and gas mining community in Wonocolo is in the ultimate means to intermediate means level, which means they are in low welfare hierarchy. It is shown by the community that still prioritized physiological needs fulfilment rather than self-development necessity. On the other hand, the fulfilment of basic needs taken from nature in Wonocolo is also vulnerable because the water and air are polluted by oil. In addition, the nature of oil that is non-renewable and unsustainable causes an economic vulnerability in Wonocolo community.